PENGARUH KREATIVITAS MENGAJAR GURU DENGAN PRESTASI BELAJAR SISWA DI SMTK BETHEL JAKARTA - Anastasia Runesi; Graciela Sharel Tanonggi; Euodia Kezia Fhanuel (Bethel Press, 2020)
Teacher teaching creativity is the teacher's ability to constantly develop material or topics and create an interesting and calm atmosphere and modify teaching. Student performance is significantly influenced by the level of creativity in teaching owned by the teacher. A teacher who teaches creativity encourages students to think critically, think outside the box, and develop creative thinking skills. This study aims to determine how much influence teacher's teaching creativity has on student achievement. This study used a quantitative method, data were collected through questionnaires to students at Bethel Jakarta High School. The results showed that the teacher's teaching creativity had quite an effect on student achievement at Bethel Jakarta Vocational High School, the teacher had a big role in creating creative teaching methods during learning so that the level of effectiveness of students in understanding the material can also be measured by how creatively the teacher conveys the material, so that things This has an effect on student achievement.